Adoption of Model Nutrition Garden by Farming Families of Punjab - Kaur, Rupinder; Kaur, Sukhjeet; Sharma, Preeti (Indian Journal of Extension Education, 2017)
The present investigation was conducted to study the extent of adoption of model nutrition garden by selected farming  families of Punjab. Ten districts were randomly selected with the help of respective KVKs. From each district, one village  was purposively selected. Twenty farmers were randomly selected from each village. The study highlighted that large  proportion of the respondents (73.2 %) used one kanal land for nutrition garden and nearly forty per cent respondents  (47%) cultivated vegetables, pulses and fruits in their nutrition garden. Adoption quotient of land used for nutrition garden  was 43 and adoption quotient of crops (vegetables, pulses and fruits) cultivated in nutrition garden was 80. The whole  adoption of model nutrition garden was 61.5 per cent. The findings revealed that technological gap for practice I (area  under nutrition garden) was 56.3 per cent and for practice II (crops cultivated in nutrition garden) was 19.6 per cent.
Keywords: Nutrition Garden; Adoption; Discontinuance; Technological Gap